2021
DOI: 10.1126/scitranslmed.abb5191
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric STAR receptors using TCR machinery mediate robust responses against solid tumors

Abstract: Chimeric antigen receptor T (CAR-T) cell therapies have demonstrated high response rate and durable disease control for the treatment of B cell malignancies. However, in the case of solid tumors, CAR-T cells have shown limited efficacy, which is partially attributed to intrinsic defects in CAR signaling. Here, we construct a double-chain chimeric receptor, termed as synthetic T cell receptor (TCR) and antigen receptor (STAR), which incorporates antigen-recognition domain of antibody and constant regions of TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 49 publications
6
72
1
Order By: Relevance
“…The incorporation of TCR-like signaling to engineered receptors has recently shown promise in multiple solid and liquid tumor models due to more controlled signaling and lower cytokine release. 20,69,70 Our data show that the TRuC platform can potentially improve the suppressive capacity of engineered Tregs in anti-drug antibody formation. The design of the next generation of antigen-specific Tregs will most likely emphasize finetuning activation in order to improve effectiveness and persistence, whereas reducing exhaustion and anergy.…”
Section: Discussionmentioning
confidence: 78%
“…The incorporation of TCR-like signaling to engineered receptors has recently shown promise in multiple solid and liquid tumor models due to more controlled signaling and lower cytokine release. 20,69,70 Our data show that the TRuC platform can potentially improve the suppressive capacity of engineered Tregs in anti-drug antibody formation. The design of the next generation of antigen-specific Tregs will most likely emphasize finetuning activation in order to improve effectiveness and persistence, whereas reducing exhaustion and anergy.…”
Section: Discussionmentioning
confidence: 78%
“…The study indicates that ATM-associated DNA-damage initiation and MAPK and STAT3 signalling activation control lipid metabolism in senescent T cells in vitro. Blockade of ATM activation with the ATM-specific inhibitor, KU55933, decreased mRNA and protein expression of group IV phospholipase A 2 α in regulatory T-induced senescent T cells [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that replacing the ζ-chain with the ε-chain of the TCR complex would improve CAR function (11,16,17). Moreover, it has been suggested that TCRlike chimeric receptors improve on the basic CAR design; by fusing the scFv directly to the extracellular domain of CD3ε (termed TruC) (18) or by replacing the variable domains of the TCR with those in the scFv (termed STAR) (19). However, accurate measurements of the relative antigen sensitivities of CARs have yet to be performed partly because it is difficult to vary the surface density of antigens on target cells.…”
Section: Introductionmentioning
confidence: 99%